2010
DOI: 10.1111/j.1540-8167.2010.01780.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Multipolar, Duty‐Cycled, Bipolar‐Unipolar Radiofrequency Versus Conventional Catheter Ablation for Treatment of Common Atrial Flutter

Abstract: The treatment of typical AFL using a hexapolar catheter with a multipolar, duty-cycled, bipolar-unipolar RF generator offers comparable effectiveness relative to conventional RF while providing improved procedural efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Another limitation of this study is that catheter systems using conventional RF energy that are available in the United States were compared in this study. It remains to be determined whether novel ablation systems and energy sources will have similar or superior efficacy than 10‐mm tip catheters 21 …”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is that catheter systems using conventional RF energy that are available in the United States were compared in this study. It remains to be determined whether novel ablation systems and energy sources will have similar or superior efficacy than 10‐mm tip catheters 21 …”
Section: Discussionmentioning
confidence: 99%
“…PDT catheter ablation in the canine CTI model required 8±4 minutes of irradiation time with 16±7 applications in this experiment, whereas the conventional radiofrequency catheter required 14.7±5.2 minutes energy delivery time with 8.9±7.2 applications in human, 23 and 3 to 4.5 minutes of 25 W radiofrequency energy delivery in a canine atrial flutter model with a surgical posterior line in advance. 13 Systemic adverse effects are also potential disadvantages of PDT ablation.…”
Section: Discussionmentioning
confidence: 99%
“…SimRFA has been reported in small case series for intramyocardial VA circuits; Yang et al recently reported the largest series to date of six patients undergoing simRFA for intramural septal VT. Both bRFA and simRFA ablation have also been used in multielectrode and circular, multipolar irrigated catheters for ablation of atrial arrhythmias and in pulmonary vein isolation (PVI) in the treatment of atrial fibrillation . In these instances, the distances between the ablation poles are smaller than the distances being targeted for deeper VA circuits.…”
Section: Introductionmentioning
confidence: 99%